2015
DOI: 10.2355/isijinternational.55.241
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Metal Types on Residual Stress in Electron-Beam Welding Joints with Sheet Metals

Abstract: The effect of metal types on the residual stresses has been researched through X-ray stress measurement for the electron-beam welding joints made of sheet metals with a thickness of approximately 10 mm. The finite-element method (FEM) has also been used to analyze the experimental results and verify the residual stress characteristics. Consequently, it has been revealed that the residual stress near the weld toe in the longitudinal direction along the weld axis becomes tensile to a larger extent as the yield s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…As a result, the extent of transverse residual stress at the weld toe, which largely affected the fatigue strength, was clarified to have relation to the weld penetration. In the second study report, 7) the transverse residual stress at the weld toe was revealed to become compressive to a larger degree as the yield strength of the testing material was higher. This tendency was observed not only for ferritic and martensitic steel materials but also for other types of metals such as SUS304 and A5052.…”
Section: Relation Between Residual Stress and Fatigue Strength For Elmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, the extent of transverse residual stress at the weld toe, which largely affected the fatigue strength, was clarified to have relation to the weld penetration. In the second study report, 7) the transverse residual stress at the weld toe was revealed to become compressive to a larger degree as the yield strength of the testing material was higher. This tendency was observed not only for ferritic and martensitic steel materials but also for other types of metals such as SUS304 and A5052.…”
Section: Relation Between Residual Stress and Fatigue Strength For Elmentioning
confidence: 99%
“…The reason the compression stress at weld toe became larger with an increase in the beam power and a decrease in the beam diameter was detailed in the past reports; 6,7) i.e., the existence of the maximum temperature region at the mechanical melting point caused the increase in the maximum tension residual stress zone in the interior of the plate, and the resultant reactive force probably generated strong compression residual stresses in the weld surface area.…”
Section: Residual Stress Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2,20) This stress distribution profile is peculiar to EBW weld joints. 6,7) The reason for such a specific stress distribution profile is due to the instantaneous formation of weld in a narrow area by the electron beam with an extremely high density energy unlike in general multi-pass arc welding. The bead surface area undergoes rapid heating and cooling to a great extent, and hence, when its high temperature part is cooled to around its mechanical melting point, the maximum temperature zone exists near the plate thickness center.…”
Section: Internal Residual Stresses In Ebw Weldsmentioning
confidence: 99%
“…As a result, the extent of the residual stress in the direction perpendicular to the weld axis at the weld toe, which largely affected the fatigue strength, was clarified to associate with the weld penetration. In the second study report, 7) the transverse residual stress at the weld toe was revealed to become compression to a larger degree as the yield strength of the testing steel grade was higher. This tendency was verified not only for ferritic and martensitic steel materials but also for other types of metals such as SUS304 and A5052.…”
Section: Introductionmentioning
confidence: 99%